Management of tomato damping-off using natural plant extracts, Trichoderma harzianum and selected fungicides in Penjween, Sulaimani Governorate, Kurdistan, Iraq - Ismael, Jalal H.S.; Mahmood, Shler H. (Malaysian Society of Applied Biology, 2016)
Tomato seedlings were found epidemically infected with damping-off disease at four locations (Kanimasyan, Kanishaban, Kanisev and Qzlja), in Penjween, Sulaimani Governorate, Kurdistan, Iraq during May 2011. The highest occurrence of disease incidence was observed in Kanimasyan (56%). Fusarium oxysporum (Schlecht), F. solani (Mart.) Sacc., F. acuminatum (Ell. and Ev.), F. equiseti (Corda) Sacc., F. compactum, Rhizoctonia solani (Kuhn), Macrophomina phaseolina (Tassi) Goid., Phoma lycopersici (Kleb), and Cephalosporium sp. were isolated from the infected plants and proved pathogenicity on tomato seeds (cv. Super Queen). Fusarium oxysporum and R. solani showed the highest level of seedling damping-off, with largest effect on decreasing the quality of seedling's vigor. Extracts of H. triquetrifolium, E. billardieri and C. rotundus at (20, 30, 40, 45 mg ml-¹) showed inhibitory effect on the mycelial growth of all pathogenic fungi. In vitro plant extract of C. rotundus revealed the highest inhibitory effects on fungal growth at 45 mg ml-¹. Fungicide of Keenol at 50 ppm proved to be chemostatic against all pathogens. T. harzianum appeared to be an important antagonistic agent against mycelial growth. Management of the disease was carried out in greenhouse using (H. triquetrifolium, Vitavax 200, T. harzianum and Keenol). It was found that the combination of (H. triquetrifolium + keenol) and (T. harzianum + H. triquetrifolium) showed impressive effects on plant height, dry and fresh weight when compared to the other treatments and control.